Experimental Analysis of PV/T Collectors Assisted with PCM for Off-Grid Domestic Applications - Bakır, Eda; Bayrak, Fatıh; Öztop, Hakan Fehmi (My University, 2021)
An experimental study was carried out to examine the efficiency of solar energy in photovoltaic thermal collectors (PV/T) with energy storage. A photovoltaic thermal collector was used to generate both electrical energy and hot water. The effects of inclination angle of PV/T collectors on power, temperature, energy and exergy values were investigated. Also, effects of cellular shading are tested and discussed. PV/T was compared with the conventional PV/T collector by adding phase change material (PCM) for one of the collectors. In addition, the effect of different shading conditions (small, medium and large circle) on the power and hot water output of the PV/T collector at optimum slope angle were investigated. It is found that 7 ºC temperature differences are occurred in the hot water outlet between the PV/T collector and the PV/T-PCM collector. The highest energy efficiencies of PV/T-PCM collectors are obtained as 73.26%, 84.70% and 68.96% for slope angle 25º, 30º and 35º, respectively. The highest exergy efficiencies of shaded collectors are obtained as 11.92% for PV/T and 23.38% for PV/T-PCM.
Keywords: Energy; Exergy; Photovoltaic/Thermal; Phase Change Material; Angle; Shading